2017
DOI: 10.1111/vox.12478
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLADRB1 and HLADQB1 with red‐blood‐cell alloimmunization in the Czech population

Abstract: For the first time, we confirmed the association of HLA-DRB1*15 with RBC antibody multiresponder status and found HLA-Class II associations for three frequent RBC antibody combinations. Our data support the concept that HLA restriction plays an important role in the response to RBC alloantigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
22
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 34 publications
15
22
5
3
Order By: Relevance
“…More recently, Maluskova and coworkers found a higher frequency of HLA‐DRB1*09 in E‐immunized persons than in controls (3.8% vs. 0.8%). In our study, HLA‐DRB1*09:01 was similarly confirmed to have a strong association with induction of anti‐E in the Chinese population …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…More recently, Maluskova and coworkers found a higher frequency of HLA‐DRB1*09 in E‐immunized persons than in controls (3.8% vs. 0.8%). In our study, HLA‐DRB1*09:01 was similarly confirmed to have a strong association with induction of anti‐E in the Chinese population …”
Section: Discussionsupporting
confidence: 78%
“…Our experimental results were consistent with the results of the other two studies on HLA‐DRB1 association and E immunization . However, the predicted results by TEPITOPEpan were not in accordance with our experiment results.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…To confirm association with only Fy a alloimmunization and not with the formation of multiple RBC antibodies, shown by other authors for DRB1*15 and DQB1*06, an analysis was performed among patients with Fy a monoresponders. Alleles DRB1*04, DRB1*15, DQB1*03 and DQB1*06 were shown to be increased, while DRB1*03 and DQB1*02 allele were decreased in patients when compared to both control groups.…”
Section: Discussionmentioning
confidence: 99%